Design single phase inverter using sinusoidal pulse width modulation (SPWM) for Automatic Transfer Switch (ATS) of solar panel and grid - Randi, Muhammad; Hendri (Journal of Industrial Automation and Electrical Engineering, 2024)
In everyday life, humans cannot live without electrical energy. Electricity has become a basic need that must be fulfilled. A backup source of electrical energy is needed when there is a disturbance of the main voltage source going out and can save electrical energy costs. This research will create a 1-phase inverter circuit using EGS002 as a sinusoidal pulse width modulation generator. SPWM is a modulation between the carrier wave and the main wave. The use of the SPWM method can also reduce the value of harmonic distortion arising from the energy conversion process. Inverter is a circuit that converts DC voltage into AC voltage in the form of a sinusoidal signal after going through wave formation and filter circuit, the resulting output voltage must be stable both the amplitude of the voltage and the frequency of the voltage produced, low distortion, no transient voltage and cannot be interrupted by a condition, the value of voltage and frequency can be adjusted To change the voltage from the main source to the backup source, a supporting device is needed in the form of an Automatic Transfer Switch (ATS). Automatic Transfer Switch (ATS) is system equipment that can regulate the alternation of electrical power supply from the main PLN power source to a backup power source or generator that works automatically by controlling the timing. This research will change the voltage from the PLN source to the backup source from the solar power plant